Production of Biogas and Bio-fertilizer from Abattoir Waste as Sustainable Management, Eastern Ethiopia, 2019 - Sina Temsgen Tolera; Fekade Ketema Alemu (Journal of Applied Sciences and Environmental Management)
Our environment facing by serious problems of high volumes of waste, inadequate disposal system particularly in developing countries worldwide. There is also lack of studies on quantification of abattoir waste and lack of workers awareness towards abattoir waste. Therefore, the purpose of the study was to estimate abattoir waste for bioenergy potential as sustainable management. A cross-sectional study was conducted in four selected abattoirs of Eastern Ethiopia from January 1st, 2018 to December 30th, 2018. The magnitude of abattoir waste composition were computed based on Aneibo mathematical computational from the actual number of  slaughtered livestock. The study demonstrated that four selected abattoirs generates 1,606,403kg of abattoir waste per year and using Fed batch Aerobic digester about and 85,139m3/year of biogas and 111,249kg/year of bio-fertilizer can be produced. The biogas or energy from the waste can replace firewood and charcoal and the expensive fossil fuels. Using Banks mathematical computation about 85,139.20m3/year of biogas estimated, could cover 36097.43kg of liquefied gas or 48129.89kg of kerosene or 280757.68kg of charcoal or 32086.59kg of furnace oil or 56151.5kg of petrol or 40108.2kg of diesel per a year in same functions. The current estimated bio-fertilizer (111,249kg/year) from four abattoir sites can cover about 2,225 hectares per a year with its advantage and efficiency of soil. When in turned into cost, about $55,645 per a year of price could estimate from biogas and bio-fertilizer. The study concluded that huge amount of biogas and dry bio-fertilizer yields could produce from abattoir waste  through fed batch anaerobic digestion. Therefore, install fed batch   anaerobic digestion plant is recommended to ensure environmental safety and public health.